Modelagem matemática do escoamento de polpa não-newtoniana bifásica em tubulações de longa distância - Sacha Maximiliano Yuno de Pompein Pessoa (2017)
The design of uid transport systems, especially of non-Newtonian multiparticulate systems and of more than one phase, are not a widespread knowledge, even for specialized companies such as mining or food industries. The purpose of this dissertation is to elaborate a general simulator for biphasic uid (solid-liquid), Newtonian or not, capable of calculating hydraulic systems (focusing on pipelines) within an acceptable margin of error. The priority results of these calculationsare: expected pressure loss, solids deposition, and homogeneous-heterogenous and laminar-turbulent transition velocities. Evaluations of rheological and hydraulic behavior of the ow are also expected. For the calculations, models found in the literature were used, and in some of them, modications, adjustments and complements were made in order to improve the precision and accuracy of existing models.In order to validate this study, was performed a statistical comparison of the simulated results with experimental data and pipeline eld measurements, in a reasonable quantities for reliable validation. The modeling has presented coherent and promising results to be used asmethodology for prediction and dimensioning of pipelines